Association between Allogeneic Blood Transfusion and Wound Infection after Total Hip or Knee Arthroplasty: A Retrospective Case-Control Study - Taneja, Ashish (J Bone Jt Infect, 2019)
Background: To assess using a retrospective case control study, whether patients undergoing primary, elective total hip or knee arthroplasty who receive blood transfusion have a higher rate of post-operative infection compared to those who do not. Materials and Methods: Data on elective primary total hip or knee arthroplasty patients, including patient characteristics, co-morbidities, type and duration of surgery, blood transfusion, deep and superficial infection was extracted from the Alberta Bone and Joint Health Institute (ABJHI). Logistic regression analysis was used to compare deep infection and superficial infection in blood-transfused and non-transfused cohorts. Results: Of the 27892 patients identified, 3098 (11.1%) received blood transfusion (TKA 9.7%; THA 13.1%). Overall, the rate of superficial infection (SI) was 0.5% and deep infection (DI) was 1.1%. The infection rates in the transfused cohort were SI 1.0% and DI 1.6%, and in the non-transfused cohort were SI 0.5% and DI 1.0%. The transfused cohort had an increased risk of superficial infection (adjusted odds ratio (OR) 1.9 [95% CI 1.2-2.9, p-value 0.005]) as well as deep infection (adjusted OR 1.6 [95% CI 1.1-2.2, p-value 0.008]). Conclusion: The odds of superficial and deep wound infection are significantly increased in primary, elective total hip and knee arthroplasty patients who receive blood transfusion compared to those who did not. This study can potentially help in reducing periprosthetic hip or knee infections.